Quantifying the control of pore types on fluid mobility in low-permeability conglomerates by integrating various experiments. (1st September 2020) - Tian, Weichao; Lu, Shuangfang; Huang, Wenbiao; Wang, Weiming; Li, Jijun; Gao, Yang; Zhan, Zhuochen; Sun, Yuefeng
Abstract: Pore types strongly influence fluid mobility of reservoirs. For a given porosity in different rocks, the movable fluid saturation can differ >30%. Previous studies commonly attribute this phenomenon to the differences in throat but ignore the importance of pore types. An effective method, which integrates nuclear magnetic resonance, LAVFS-SEM and nitrogen gas adsorption experiments, was established to quantitatively investigate the abundance and size distributions of different pore types, and their control on fluid mobility in conglomerates from the Mahu Sag, China. Furthermore, the geological control of intergranular (dissolution) pores (InterG-Ds) is analyzed. The pores characterized by N2 GA are mainly clay-related pores (CRPs), and the shape of hysteresis loop is related to the type of clay minerals. InterG-Ds are mainly distributed > 1 μm, corresponding to the P3 and P2 in T2 spectrum. Intragranular dissolution pores range from tens of nanometers to ten micrometers, associated with P2 and P1. CRPs are below 900 nm and associated with P1. The content of InterG-Ds controls fluid mobility of conglomerates. 190 × 10 −4 mL/g is the lower limit of InterG-D volume, which can judge that the continuous percolation network (CPN) is composed by only InterG-Ds. 45 × 10 −4 mL/g is the upper limit of the InterG-D volume to determine that the CPN consists of only CRPs. With the decrease of InterG-D volume, both movable fluid porosity and permeability reduce. Good sorting and abundant rigid particles are prerequisites for the development of InterG-Ds. Cementation can significantly reduce InterG-Ds volume, while feldspar dissolution can increase InterG-D volume.